Innate immunity of bile and cholangiocytes in primary biliary cholangitis - Chen, Ran; Sun, Yan; Hu, Ying; Tai, Wenlin (Frontiers in Immunology, 2025)
Primary Biliary Cholangitis (PBC) is a chronic autoimmune liver disease characterized by immune-mediated destruction of intrahepatic bile ducts. This review synthesizes current knowledge on the critical role of innate immunity, specifically involving cholangiocytes, bile components, and associated immune cells. Cholangiocytes function not only as passive targets but also as active immunomodulators through mechanisms including Toll-like receptor (TLR) signaling, antigen presentation, and immune cell recruitment. Dysregulated bile acid signaling via receptors like TGR5 disrupts immune homeostasis, while apoptosis of biliary epithelial cells releases antigens (e.g., PDC-E2), triggering aberrant innate and adaptive immune responses. Innate lymphoid cells (ILCs), natural killer (NK) cells, and macrophages exhibit altered frequencies and functions in PBC, driving chronic inflammation and fibrosis through cytokine cascades (e.g., IL-17, IFNγ) and interactions within the gut-liver axis. Furthermore, biliary microbiota dysbiosis exacerbates disease by promoting bacterial translocation, modifying bile acid metabolism, and activating innate immune pathways. Current clinical management with ursodeoxycholic acid (UDCA) and obeticholic acid (OCA) primarily addresses cholestasis. However, the immunomodulatory effects of these agents remain constrained. Targeted therapeutic strategies addressing innate immune pathways—exemplified by RIPK2 (Receptor Interacting Serine/Threonine Kinase 2) inhibition, IL-1 blockade(Canakinumab), and T cell immunoglobulin mucin domain-containing protein 3 (TIM-3) modulation—alongside cell-based interventions such as mesenchymal stem cell therapy, demonstrate considerable therapeutic potential. Advancing these modalities necessitates multidisciplinary integration to facilitate clinical translation. Additionally, Prognostic indices like the neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-lymphocyte ratio (MLR) reflect systemic inflammation and correlate with disease progression. Achieving therapeutic precision requires deeper elucidation of the gut-biliary-immune axis, trained immunity mechanisms, and cholangiocyte senescence, paving the way for targeted interventions in PBC. Establishing a comprehensive treatment burden assessment system is imperative to facilitate the transition from investigational platforms to clinical care.